Imipenem/Relebactam Ex Vivo Clearance during Continuous Renal Replacement Therapy - Soo Min Jang; Lenar Yessayan; Michael Dean; Gabrielle Costello; Ravi Katwaru; Bruce A. Mueller (MDPI AG, 2021)
(1) Purpose of this study: determination of adsorption and transmembrane clearances (CLTM) of imipenem and relebactam in ex vivo continuous hemofiltration (CH) and continuous hemodialysis (CHD) models. These clearances were incorporated into a Monte Carlo Simulation (MCS), to develop drug dosing recommendations for critically ill patients requiring continuous renal replacement therapy (CRRT); (2) Methods: A validated ex vivo bovine blood CH and CHD model using two hemodiafilters. Imipenem/relebactam and urea CLTM at different ultrafiltrate/dialysate flow rates were evaluated in both CH and CHD. MCS was performed to determine dose recommendations for patients receiving CRRT; (3) Results: Neither imipenem nor relebactam adsorbed to the CRRT apparatus. The CLTM of imipenem, relebactam, and urea approximated the effluent rates (ultrafiltrate/dialysate flow rates). The types of hemodiafilter and effluent rates did not influence CLTM except in a dialysis flow rate of 1 L/h and 6 L/h in the CHD with relebactam (p < 0.05). Imipenem and relebactam 200 mg/100 mg every 6 h were sufficient to meet the standard time above the MIC pharmacodynamic targets in the modeled CRRT regimen of 25 kg/mL/h. (4) Conclusions: Imipenem and relebactam are not removed by adsorption to the CRRT apparatus, but readily cross the hemodiafilter membrane in CH and CHD. Dosage adjustment of imipenem/relebactam is likely required for critically ill patients receiving CRRT.